Eksaminasi pertimbangan hakim terhadap Putusan Tindak Pidana Perdagangan Orang (Studi kasus putusan No. 39/Pid. Sus/2024/PN Wat) - Toufan Jati Kumoro SUNARDI; Muhammad Azil Maskur Azil Maskur (Universitas Negeri Semarang, 2025)
Human trafficking is a form of transnational crime that violates human rights, particularly those of vulnerable groups such as women and children, and continues to increase in Indonesia. According to the Global Slavery Index 2023, Indonesia is estimated to have around 1.8 million victims of human trafficking, making it one of the countries with the highest number of cases in Southeast Asia (Walk Free Foundation, 2023)[1]. Although Indonesia has enacted Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking (UU PTPPO), the practical implementation of victim protection within the judicial system still faces significant challenges. This article aims to provide a juridical analysis of victim protection in Decision No. 39/Pid.Sus/2024/PN.Wat issued by the Wates District Court. The research method used is normative juridical, combined with a case study approach and comparative analysis of victim protection principles in both national and international law. The findings indicate that although the court has adequately considered the criminal elements, victim protection has not been fully maximized, especially in terms of rehabilitation, psychological.